Cascading Geological Hazards and Risks of the 2018 Sulawesi Indonesia Earthquake and Sensitivity Analysis of Tsunami Inundation Simulations - Katsuichiro Goda (Frontiers in Earth Science, 2019)
Multiple cascading hazards triggered by the 2018 Sulawesi, Indonesia, earthquake caused various compounding consequences. A major strike-slip fault movement with along-dip components resulted in intense ground shaking, liquefaction and lateral spreading, large-scale mudflows, and tsunamis. This paper presents observations of such multi-hazard effects on buildings and infrastructure in areas along Palu Bay, based on field reconnaissance work, and discusses the main causes of the disaster by focusing upon the combined effects of the cascading geological hazards. To evaluate the tsunami risk potential of the strike-slip event, tsunami simulations for the 2018 Sulawesi earthquake are performed by considering different model settings for spatial earthquake slip distribution, rake angle, astronomical tidal effect, and co-seismic ground deformation. The numerical results indicate that the co-seismic rupture of a moment magnitude 7.5 strike-slip earthquake, having notable dip components can generate damaging tsunami waves at coastal locations of Palu Bay. The conclusion has important implications for future tsunami hazard assessments in active seismic regions where major fault systems cut across a bay or into the sea.